Relaxed Stability and Stabilization Conditions of Networked Fuzzy Control Systems Subject to Asynchronous Grades of Membership - Peng, Chen; Yue, Dong; Fei, Min-Rui (IEEE transactions on fuzzy systems, 2014)
This paper presents relaxed stability and stabilization conditions for Takagi-Sugeno (T-S) fuzzy systems under network environments subject to asynchronous grades of membership. Because of the introduction of a communication network, the favorable property in the point-to-point connection, that is, sharing the identical premises in the fuzzy plant and the fuzzy controllers cannot be arbitrarily employed. To widen the applicability of the fuzzy control method under network environments, a novel method is provided to reconstruct the synchronous time scale grades of membership at the controller as those in the plant. As a result, the aforementioned favorable property can be conditionally used in the derivation of the stability and stabilization criteria for the system under consideration controlled over a communication network. Numerical examples have been given to illustrate the effectiveness of the proposed approach.